In vitro expansion of single Lgr5+ liver stem cells induced by Wnt-driven regeneration - Huch, Meritxell (2013)
The Wnt target gene Lgr5 marks actively dividing stem cells in Wnt-driven, self-renewing tissues such as small intestine and colon(1), stomach(2) and hair follicles(3). A 3D culture system allows long-term clonal expansion of single Lgr5(+) stem cells into transplantable organoids that retain many characteristics of the original epithelial architecture(2, 4, 5). A crucial component of the culture medium is the Wnt agonist Rspo1(6), the recently discovered ligand of Lgr5(7, 8). Here we show that Lgr5-LacZ is not expressed in healthy adult liver, yet that small Lgr5-LacZ(+) cells appear near bile ducts upon damage, coinciding with robust activation of Wnt signaling. As shown by lineage tracing using a novel Lgr5-ires-CreERT2 knock-in allele, damage-induced Lgr5(+) cells generate hepatocytes and bile ducts in vivo. Single Lgr5(+) cells from damaged liver can be clonally expanded as organoids in Rspo1-based culture medium over multiple months. Such clonal organoids can be induced to differentiate in vitro and to generate functional hepatocytes upon transplantation into FAH(−/−) mice. These findings imply that previous observations on Lgr5(+) stem cells in actively self-renewing tissues extend to damage-induced stem cells in a tissue with a low rate of spontaneous proliferation.